Intercropping Systems Modify Desert Plant-Associated Microbial Communities and Weaken Host Effects in a Hyper-Arid Desert - Zhang, Zhihao; Chai, Xutian; Tariq, Akash; Zeng, Fanjiang; Li, Xiangyi; Graciano, Corina (Frontiers in Microbiology, 2021)
Intercropping is an important practice in promoting plant diversity and productivity. Compared to the accumulated understanding of the legume/non-legume crop intercrops, very little is known about the effect of this practice when applied to native species on soil microbial communities in the desert ecosystem. Therefore, in the present study, bulk soil and rhizosphere microbial communities in the two-year Alhagi sparsifolia (legume)/Karelinia caspica (non-legume) monoculture vs. intercropping systems were characterized under field conditions. Plant species identities exerted a minor effect on microbial communities (P>0.05). Fungal communities were primarily structured by planting patterns, while bacterial communities responded mainly to soil compartments and planting patterns, as reflected in β-diversity (P<0.05). Deterministic processes dominated bacterial community assembly, which was marginally affected by planting patterns and soil compartments. Microorganisms sensitive to planting patterns were taxonomically diverse, with some taxa (e.g., Firmicutes) responding to specific planting patterns. These microbes also included keystone taxa that prevailed in bulk soil and were bacteria-dominated. Overall, planting patterns and soil compartments, not plant identities, were found to differentiate root-associated microbiomes. Intercropping can induce more key functional microbial groups into desert soil communities. These findings provided a potential strategy for us to manipulate desert soil microbial communities and optimize desert species allocation in vegetation sustainability.